Prospects for research, policymaking, and urban design practice on active travel to/from school - Barros, Paula; Guerra, Paulo Henrique [UNESP]; Khan, Matluba; Fermino, Rogério César (Elsevier, 2024)
Active travel to/from school (ATS) is complex and critical to child health. Hence, the well-documented decline in ATS across the globe has become a significant public health. Informed by an overview of systematic reviews on the inter-relationships between ATS and the health of children and adolescents, this commentary addresses the following questions: Where next for research moving ahead? What to consider when putting all the knowledge available into policymaking? What is the value of evidence-based urban design participatory processes to promote ATS in healthy environments? A strength of this commentary has been its interdisciplinary nature. Working across disciplines––public health, physical education, architecture, urban planning, and urban design––led to the proposal of relevant research agendas, prospects for policymaking based on the knowledge available, and reflections on the role of urban design in promoting ATS and health.
Keywords: Active travel to school; Health; Physical activity; Review; Urban design